Modelling and investigation of metal mixing in an active ladle - Velychko , K.O.; Grek , A.S.; Tokarev , S.I. (Theory and Practice of Metallurgy, 2024)
The processes of mixing in a ladle during blowing through a top lance have been studied in laboratory conditions on a “cold” model. It is confirmed that the efficiency of mixing during blowing is determined by the gas flow rate and the position of the top lance. It is proposed to simultaneously rotate the ladle around its own axis during gas blowing in the ladle. In this case, a design of a rotating ladle with a protrusion on the bottom from the axis to the wall was developed. The influence of the ladle rotation, including the ladle with a protrusion on the bottom, on the mixing efficiency was studied. It was found that the ladle rotation makes it possible to reduce the duration of chemical composition averaging by 2 times or more. The developed method is effective when injecting alloying materials and desulphurisers at complex steel finishing units.